Postharvest Handling of Horticultural Crops (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The postharvest handling of horticultural produce is of major importance because fresh fruit and vegetables are highly perishable. It is estimated that 30% of produced horticultural commodities are lost in processes between harvest and consumption, and the reduction in these losses is currently imperative because it will impact the amount of produced food, introducing benefits on agricultural inputs, water, and land use and contributing to the sustainability of agriculture and the planet. The Special Issue “Postharvest handling of horticultural produce” collects a series of recent research papers focusing on the ripening of fruit and the senescence of harvested horticultural products, in addition to the development of environmentally friendly products and technologies that positively impact the quality and shelf life of those products, improving consumers’ preference. This Special Issue provides a valuable contribution for understanding horticultural products’ postharvest physiology and the implementation of new innovative technologies for reducing quality loss through the supply chain. In this manner, this Special Issue contributes to reductions in food loss, promoting the sustainability of agriculture.